2017
DOI: 10.1186/s13620-017-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of plasma proteins in dairy cows with subclinical hypocalcaemia

Abstract: Subclinical hypocalcaemia (SH) is an important metabolic disease in dairy cows that has a serious impact on production performance. The objective of this study was to investigate novel aspects of pathogenesis using proteomics technology to identify proteins that are differentially expressed in diseased and healthy animals. Dairy cows were divided into an SH group (T, n = 10) and a control group (C, n = 10) based on plasma calcium concentration. A total of 398 differentially expressed proteins were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Similarly, MIR spectral data has been used to estimate the Ca and P concentration of milk with reasonable accuracy (Toffanin et al, 2015); however, its ability to predict serum Ca and Mg concentrations was poor. Studies have demonstrated that animals suffering from subclinical hypocalcemia showed significant changes in their serum proteome (Wang et al, 2016;Fan et al, 2017). Given that changes in serum albumin and globulin concentrations could not be identified with milk MIR spectra, it follows that changes in serum proteome associated with hypocalcemia are also not detectable using milk MIR spectral analysis.…”
Section: Pls Regression Models For Predicting Serum Metabolite Concenmentioning
confidence: 99%
“…Similarly, MIR spectral data has been used to estimate the Ca and P concentration of milk with reasonable accuracy (Toffanin et al, 2015); however, its ability to predict serum Ca and Mg concentrations was poor. Studies have demonstrated that animals suffering from subclinical hypocalcemia showed significant changes in their serum proteome (Wang et al, 2016;Fan et al, 2017). Given that changes in serum albumin and globulin concentrations could not be identified with milk MIR spectra, it follows that changes in serum proteome associated with hypocalcemia are also not detectable using milk MIR spectral analysis.…”
Section: Pls Regression Models For Predicting Serum Metabolite Concenmentioning
confidence: 99%
“…Many studies have found that BHBA is a predominant and stable blood ketone body in ruminant ketosis [4,10], which, therefore, has been widely used for clinically diagnosing and classifying ketosis in dairy cows [11]. Furthermore, a large number of molecular biomarkers have been also identified to be associated with ketosis, such as milk fatty acids [12], serum hepatokines [13], inflammatory biomarkers [14], methylglyoxal [2], metabolites [15], mineral elements [16], protein profiling [17], and amino acids [18] in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Moyes et al (2013) used isobaric tags for relative and absolute quantitation based quantitative profiling of cow liver tissue and found potential hepatic biomarkers for different degrees of physiological imbalance of dairy cows in early and mid-lactation. Using the same method, Fan et, al (Fan et al, 2017) identified differentially expressed proteins related to a metabolic disorder of subclinical hypocalcemia. Moreover, proteomic analysis using liver tissues (Xu and Wang, 2008) and adipose tissues (Xu et al, 2019) has also been used in cow ketosis studies, which would provide novel opportunities to unravel the complex biology of the disease.…”
Section: Introductionmentioning
confidence: 99%